Interferensi Bahasa Melayu Batubara terhadap Kemampuan Berbahasa Indonesia Siswa SMA - NFN Sahril; Susy Deliana (SUAR BETANG, 2019)
Indonesia has a diversity of languages in each region so the use of language triggers interference. Interference occurs because a speaker has not fully understood the context of the language used. Judging from the performance, the speaking skills of high school students in Batubara Regency in local languages are more dominant than those in Indonesian language. Thus, regional language interference as a more dominant language can occur in Indonesian in students' speaking skills. This study aims to describe the interference of the Malay dialect of Malay in the ability of high school students in Batubara. As well as describing the factors and functions of Malay Batubara dialect interference in Indonesian. The findings of this study were phonological, morphological, syntactic, and semantic interference by high school students in Batubara District. There are nine factors for interference. The presence of interference in the speech of high school students in Batubara taken place for several reasons, namely to emphasize the meaning, to express feelings of emotion and to respect the speech partner.AbstrakBangsa Indonesia memiliki keanekaragaman bahasa di setiap daerah sehingga penggunaan bahasa memicu timbulnya interferensi. Interferensi terjadi karena seseorang penutur belum memahami sepenuhnya konteks bahasa yang digunakan. Dilihat dari perfomansi, keterampilan berbicara siswa SMA di Kabupaten Batubara dalam bahasa daerah lebih dominan dibandingkan dengan keterampilan berbicara dalam bahasa Indonesia. Dengan demikian, interferensi bahasa daerah sebagai bahasa yang lebih dominan dapat terjadi dalam bahasa Indonesia pada keterampilan berbicara siswa. Penelitian ini bertujuan untuk mendeskripsikan interferensi bahasa Melayu dialek Batubara terhadap kemampuan siswa SMA di Batubara serta mendeskripsikan faktor dan fungsi interferensi Melayu dialek Batubara dalam bahasa Indonesia. Temuan penelitian ini ialah adanya interferensi fonologis, morfologis, sintaksis, dan semantik oleh siswa SMA di Kabupaten Batubara. Hadirnya interferensi dalam tuturan siswa SMA di Batubara ini didasari oleh beberapa alasan, yaitu untuk menekankan makna, untuk mengungkapkan perasaan emosi, dan untuk menghormati mitra tutur.